Recent Trends in Lending for Civil Service Reform - Manning, Nick; Mukherjee, Ranjana (World Bank, Washington, DC, 2012)
The note assesses how the volume, distribution, structure, and objectives of Bank lending for civil service reform have changed in recent years. Bank operations in civil service reform usually refers to interventions that affect the organization, performance, and working conditions of employees paid by government budgets, but excludes reforms that affect police, the armed forces, public health care workers, public school teachers, and employees of state enterprises. Assessments of such reform are relevant in that they can also help countries improve governance, thus fostering good policy making, effective service delivery, and accountable resource use. Findings based on an Operations Evaluation Department's review of such lending, indicates a growing number of standalone civil service reform projects between 1980 and 1997. However, between fiscal 1999 and 2001, only 4 of 62 civil service reform interventions were standalone, being the rest components of major lending operations. The note further reviews the distribution of new lending, and its structure, categorizing civil service reform objectives under three broad headings: correcting fiscal imbalances, adjusting civil servant's pay, and grading structures to improve accountability, and service delivery. Issues for further consideration are raised: what are the optimal combinations - investment lending vs. programmatic adjustment - of such financing, and under what circumstances? and, in identifying the structure of the overall, changing portfolio, what would the impact be?